Advances in Antiferromagnetic Spintronics - Hirohata, Atsufumi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Antiferromagnetic spintronics is an emerging topic in spintronics that is attracting interest due to its wide range of advantages, including terahertz operation, memory without stray fields, and highly efficient spin generation. The discussion of this topic covers aspects ranging from the development of new antiferromagnetic materials to the applications of these materials in devices. Traditionally, antiferromagnets were treated as less common magnetic materials for fundamental studies and applications. However, recent miniaturisation and high-frequency operation have revealed that they are advantageous over conventional ferromagnets. This Special Issue reviews the current status and future perspectives of antiferromagnetic spintronics.